A Lack of Palliative Therapy Use in Patients With Advanced Penile Cancer. Issue 2 (April 2021) - Davaro, Facundo M.; Weinstein, David; Siddiqui, Sameer A.; Hamilton, Zachary A.
Objectives: Advanced penile cancer is associated with a poor prognosis; therefore, providing patients with realistic expectations, addressing goals of care and offering palliative therapy when appropriate is critical. Our goal was to investigate the National Cancer Database (NCDB) and analyze the role and trends in use of palliative therapy in patients with advanced penile cancer. Methods: The NCDB 2004−2015 penile cancer data set was queried for patients with locally advanced, defined as cT4NanyM0 and cTanyN3M0, or metastatic disease regardless of tumor or nodal stage. Patients were categorized based on whether they did or did not receive palliative care. Palliative care was cataloged as pain management therapy, surgery, radiation or systemic treatment, any combination therapy or not otherwise specified (NOS). Our primary outcome was receiving palliative therapy. Secondary outcome was the temporal trends in palliative care. Logistic regression (LR) was performed. Results Obtained: 385 and 279 patients were identified with locally advanced and metastatic penile cancer respectively. 27 (7.1%) and 49 (17.6%) patients received palliative care. Average age of patients accepting palliative care was 61.9 years old, about 5 years younger than their counterparts who declined therapy (p < 0.011) in the metastatic cohort. Other patient specific demographics and clinical tumor characteristics were not significantly different in either population. Of patients with locally advanced disease pursuing palliative therapy, radiation (29.6%), surgery (14.8%), systemic treatment (14.8%) and combination treatment (22.2%) were the more popular choices. In the metastatic population, radiation (32.7%) and systemic therapy (24.5%) were the most prevalent choices for palliative treatment followed by combination treatment (16.3%), surgery (12.2%), pain management (10.2%), or NOS (4.1%). LR for the receipt of "any palliative therapy" revealed that increasing age (OR 0.971, p = 0.032) decreased the likelihood of accepting palliative therapy in the metastatic population but not in the locally advanced group. Charlson score of 2 (OR 5.966, p = 0.025) and low income (OR 3.968, p = 0.002) predicted receipt of palliative therapy in the locally advanced group. In patients with metastatic disease, African-American race (OR 2.502, p = 0.025), Charlson score 1 (2.175, p = 0.047) and 3+ (5.386, p = 0.020) predicted an increased predilection for receiving palliative therapy. Interestingly, no statistically significant difference in mortality was noted in either cohort. No significant increase in the trend of palliative care administration was seen in locally advanced and metastatic penile cancer between 2004 to 2015 (p = 0.078 and p = 0.942, respectively). Conclusion: Locally advanced and metastatic penile cancer carry a high mortality rate yet only 11.4% of all patients studied received palliative care. Its use is more common in younger patients, those with co-morbidities and/or those of black race in the metastatic group. Locally advanced patients with low income or comorbidities were also more likely to opt for palliative therapy. Receipt of palliative care did not affect mortality. No increase in frequency of palliative therapy was seen, suggesting much improvement needs to be done in adopting and implementing palliative care in this patient population.